RESPONS PERTUMBUHAN DAN PRODUKSI KACANG TANAH TERHADAP BAHAN ORGANIK Tithonia diversifolia DAN PUPUK SP-36 - Budi Surya Lumban Raja Budi Surya Lumban Raja Budi Surya Lumban Raja; B. S. J. Damanik; Jonis Ginting (Jurnal Agroekoteknologi, 2013)
Peanut is one of food plant that has high economical value because of its nutrient content especiallyprotein and fat. The other alternative to increase peanut productivity were application of Tithoniadiversifolia organic matter and SP-36 fertilizer. The aim of the study was to obtain the effect ofapplication Tithonia diversifolia organic matter and SP-36 fertilizer on growth and yield of peanut.The study was conducted at Jl. Pasar I Tanjung Sari, Medan with the height 25 metres abovesea level from May to September 2012. The factorial randomized block design was used twofactors, namely Tithonia diversifolia organic matter (0, 3, 6 and 9 ton/ha) and SP-36 (0, 25, 50, 75and 100 kg/ha). The parameters observed were number of ginofor per sample, number of filled podsper sample, number of empty pods per sample, weight of pods per sample, yield per plot and 100grain weight. The results showed that the Tithonia diversifolia organic matter had no significanteffect on all parameters and SP-36 fertilizer significantly affected 100 grain weight. Interaction ofthat treatment had no significant effect on all parameters.Key words : peanut, Tithonia diversifolia , organic matter, SP-36 fertilizer